Принципи кодифікації національного фармацевтичного законодавства - Алексєєв, Олександр Германович; Alexeev, O. G. (My University, 2010)
У статті розглядаються питання реформування фармацевтичного законодавства України шляхом його кодифікації. Наведено класифікацію загальних принципів кодифікації, дотримання яких, на думку автора, дозволить зважено підійти до процесу систематизації фармацевтичного законодавства шляхом його кодифікації. Questions connected with reforming of the pharmaceutical legislation of Ukraine by its codification are considered. Classification of the general principles of the codification, which observance, by definition of the author is resulted, will allow to approach to process of ordering of the pharmaceutical legislation by its codification.
The principles of codification of the pharmaceutical legislation
Keywords: адміністративна реформа; фармацевтичне законодавство; систематизація; принципи кодифікації; administrative reform; the pharmaceutical legislation; ordering; codification principles